1993
DOI: 10.1073/pnas.90.12.5653
|View full text |Cite
|
Sign up to set email alerts
|

Rapid in vitro selection of human immunodeficiency virus type 1 resistant to 3'-thiacytidine inhibitors due to a mutation in the YMDD region of reverse transcriptase.

Abstract: Resistant variants of human immunodeficiency virus type 1 (HIV-1) have been selected by limited passage in MT4 cells of both wild-type and 3'-azido-3'-deoxythymidine (AZT, zidovudine)-resistant strains with the nucleoside analogues (-)-2'-deoxy-3'-thiacytidine (3TC) and (-)-2'-deoxy-5-fluoro-3'-thiacytidine (FTC). Virus variants selected independently were crossresistant to both inhibitors. This rapid in vitro selection of resistant virus has not previously been seen with nucleoside analogues but is reminiscen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
469
2
4

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 569 publications
(490 citation statements)
references
References 27 publications
15
469
2
4
Order By: Relevance
“…The close proximity of Tyr-183 and Met-184 to the active site of the aspartic acid triad of HIV-1 RT can affect the fidelity of DNA synthesis. It is important to note that modifications of Met-184 in HIV-1 RT were reported to confer resistance to ddCTP, ddlTP and oxathiolane-cytosine nucleotides [34][35][36]. We have found that both the MI84L and Y183F mutants show also a significant reduction in sensitivity to ddNTPs (unpublished results).…”
Section: Discussionmentioning
confidence: 73%
“…The close proximity of Tyr-183 and Met-184 to the active site of the aspartic acid triad of HIV-1 RT can affect the fidelity of DNA synthesis. It is important to note that modifications of Met-184 in HIV-1 RT were reported to confer resistance to ddCTP, ddlTP and oxathiolane-cytosine nucleotides [34][35][36]. We have found that both the MI84L and Y183F mutants show also a significant reduction in sensitivity to ddNTPs (unpublished results).…”
Section: Discussionmentioning
confidence: 73%
“…For the other child receiving AZT and 3TC some relevant resistance codons were missing from evaluation, thus hampering the final result interpretation. However, she also presented the T215Y-mediated AZT resistance, which is reversed by the M184V mutation (Tisdale et al 1993). The T69D was detected in 1 child.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a mutation may reverse the effect of another mutation occurring concurrently in a viral variant. This is the case for the 3TC resistance mutation M184V, which can reverse the effect conferred by the ZDV mutation T215Y (1,14,28). Thus, although resistance to a particular antiretroviral drug is conferred by a specific mutation(s) associated with a particular drug, this can also be modulated by other mutations present in the background.…”
mentioning
confidence: 99%
“…For example, mutations at codons 41, 67, 70, 210, 215, and 219 of reverse transcriptase (RT) typically confer resistance to zidovudine (ZDV) (6,12,13,27). Similarly, mutation M184V in RT has been shown to be specifically associated with high-level (Ն50-fold) phenotypic resistance to lamivudine (3TC) (1,22,28). No "specific" mutation(s) associated with moderate levels of phenotypic resistance (4-to Ͻ50-fold) to 3TC has been described before.…”
mentioning
confidence: 99%